Hybrid Model Predictive Control of Exhaust Recompression Hcci. Issue 2 (8th May 2013) - Widd, Anders; Liao, Hsien‐Hsin; Gerdes, J. Christian; Tunestål, Per; Johansson, Rolf
Abstract Homogeneous charge compression ignition (HCCI) holds promise for reduced emissions and increased efficiency compared to conventional internal combustion engines. As HCCI lacks direct actuation over the combustion phasing, much work has been devoted to designing controllers capable of set‐point tracking and disturbance rejection. This paper presents results on model predictive control (MPC) of the combustion phasing in an HCCI engine based on a hybrid model formulation composed of several linearizations of a physics‐based nonlinear model. The explicit representation of the MPC was implemented experimentally and the performance during set point changes was compared to that of a switched state feedback controller. The hybrid MPC produced smoother transients without overshoot when the set point change traversed several linearizations.